2022
DOI: 10.1021/acs.jmedchem.2c00325
|View full text |Cite
|
Sign up to set email alerts
|

Protein Lysine Methyltransferase SMYD2: A Promising Small Molecule Target for Cancer Therapy

Abstract: In epigenetic research, the abnormality of protein methylation modification is closely related to the occurrence and development of tumors, which stimulates the interest of researchers in protein methyltransferase research and the efforts to develop corresponding specific small molecule inhibitors. Currently, the protein lysine methyltransferase SMYD2 has been identified as a promising new small molecule target for cancer therapy. But its biological functions have not been fully studied and relatively few inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…SMYD2, as a classic lysine methyl transferase, can regulate cell behavior by depositing methyl groups on histones H3K36 and H3K4, and SMYD2 was recently verified can catalyze diverse nonhistone protein substrates. [10][11][12][13] Multiple studies confirmed SMYD2 can abnormally regulate carcinoma-related genes to promote the development and progression of various tumors. [14][15][16]18,21,36 Our study identifies SMYD2 as an oncogenic gene in PCa, wherein aberrant upregulation of SMYD2 was observed in PCa tissues compared with benign tissues and high SMYD2 expression was a risk factor for biochemical recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…SMYD2, as a classic lysine methyl transferase, can regulate cell behavior by depositing methyl groups on histones H3K36 and H3K4, and SMYD2 was recently verified can catalyze diverse nonhistone protein substrates. [10][11][12][13] Multiple studies confirmed SMYD2 can abnormally regulate carcinoma-related genes to promote the development and progression of various tumors. [14][15][16]18,21,36 Our study identifies SMYD2 as an oncogenic gene in PCa, wherein aberrant upregulation of SMYD2 was observed in PCa tissues compared with benign tissues and high SMYD2 expression was a risk factor for biochemical recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…SMYD2, as a classic lysine methyl transferase, can regulate cell behavior by depositing methyl groups on histones H3K36 and H3K4, and SMYD2 was recently verified can catalyze diverse nonhistone protein substrates 10–13 . Multiple studies confirmed SMYD2 can abnormally regulate carcinoma‐related genes to promote the development and progression of various tumors 14–16,18,21,36 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations